Bariery finansowania projektów realizowanych przez podmioty polskie z funduszy strukturalnych Unii Europejskiej - Ładysz, Jerzy (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The aim of research was the identification of barriers which make difficult financing and realization of projects co-financed by European Union structural funds. These barriers have negative influence on the competitiveness of Polish economy in relation to economies of other states embraced with common structural policy. Minimizing of influence or overcoming the barriers which appear at realization of projects supported from structural funds should be supported by the state's economic policy (similarly as in other member states of the EU). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 229-235